Morphological and Genotypic Characterization Of Different Lotus (Nelumbo Nucifera Gaertn.) Samples Available in Bangladesh (Bangladesh Journal of Plant Taxonomy, 2022)
Asian lotus (Nelumbo nucifera Gaertn.), commonly known as sacred lotus is a basal eudicot. It has been grown and cultivated as food, medicine and for cultural, and religious activities. In the current study, samples were collected from six different locations to evaluate the variation among different lotus germplasm based on external morphological characteristics, as well as, to study the genetic variation and the molecular characterization. Analysis of variance showed a higher level of variations among the germplasm for all the morphological features. Based on the morphological features, a dendrogram was constructed to assess the linkage among the germplasm. The yellow lotus of Cumilla was considered superior among the germplasm studied. To assess the genetic diversity and the correct identification of lotus germplasm, molecular method “Barcoding” was performed. To achieve the goal, two plastidial regions: rpoB and rpoC1 were employed. The germplasm showing successful PCR were subjected to sequence analysis of their barcode genes. All the selected barcode genes showed successful identification of all the germplasm as N. nucifera in multilocus identification based on their sequences except for the germplasm of Rajshahi and also confirmed the yellowish lotus of Cumilla considered as a new cultivar N. nucifera ‘Gomoti’, newly found in Bangladesh. Genetic sequences obtained in the context of DNA barcoding had also been used to create a phylogenetic tree in which the germplasm were clustered into five main clades. The current study was successful in establishing an efficient protocol for the correct identification of lotus germplasm and was capable of establishing an elite gene source. Moreover, future studies are warranted to see the identifying capability and diverging power of the barcodes.Bangladesh J. Plant Taxon. 29(1): 85-95, 2022 (June)